Clay swelling of Quaternary and Paleogene deposits in the south-eastern flanks of West Siberian iron ore basin - Kramarenko, Violetta Valentinovna; Shinawi, A.El.; Matveenko, Irina Alekseevna; Shramok, A.A. (IOP Publishing, 2016)
Revealing soil swelling and estimation of swelling rate are of great importance at the initial survey stages as well as the bases for further determination of more accurate factors used for selection of recovery methods and facility design. The paper states briefly the most conventional prediction express-methods and determination of swelling indicators, the results of laboratory research in clay composition and properties, free swell index of Quaternary and Paleogene clays in the south-east of West Siberian iron-ore, gives the estimates of the swelling rate. The results have been statistically analyzed, revealing the relationship of properties, on the basis of which the correlation dependencies are suggested to predict the free swell index as well as to apply it for frost heave prediction.
Keywords: глины; четвертичные отложения; палеогеновые отложения; Западно-Сибирский железорудный бассейн; почвы; набухание; пучение; Кайнозой::Четвертичная; Кайнозой::Палеоген